Endogenous Fructose Metabolism Could Explain the Warburg Effect and the Protection of SGLT2 Inhibitors in Chronic Kidney Disease - Nakagawa, Takahiko; Sanchez-Lozada, Laura G.; Andres-Hernando, Ana; Kojima, Hideto; Kasahara, Masato; Rodriguez-Iturbe, Bernardo; Bjornstad, Petter; Lanaspa, Miguel A.; Johnson, Richard J. (Frontiers in Immunology, 2021)
Chronic low-grade inflammation underlies the pathogenesis of non-communicable diseases, including chronic kidney diseases (CKD). Inflammation is a biologically active process accompanied with biochemical changes involving energy, amino acid, lipid and nucleotides. Recently, glycolysis has been observed to be increased in several inflammatory disorders, including several types of kidney disease. However, the factors initiating glycolysis remains unclear. Added sugars containing fructose are present in nearly 70 percent of processed foods and have been implicated in the etiology of many non-communicable diseases. In the kidney, fructose is transported into the proximal tubules via several transporters to mediate pathophysiological processes. Fructose can be generated in the kidney during glucose reabsorption (such as in diabetes) as well as from intra-renal hypoxia that occurs in CKD. Fructose metabolism also provides biosynthetic precursors for inflammation by switching the intracellular metabolic profile from mitochondrial oxidative phosphorylation to glycolysis despite the availability of oxygen, which is similar to the Warburg effect in cancer. Importantly, uric acid, a byproduct of fructose metabolism, likely plays a key role in favoring glycolysis by stimulating inflammation and suppressing aconitase in the tricarboxylic acid cycle. A consequent accumulation of glycolytic intermediates connects to the production of biosynthetic precursors, proteins, lipids, and nucleic acids, to meet the increased energy demand for the local inflammation. Here, we discuss the possibility of fructose and uric acid may mediate a metabolic switch toward glycolysis in CKD. We also suggest that SGLT2 inhibitors may slow the progression of CKD by reducing intrarenal glucose, and subsequently fructose levels.